Wear Resistance of Anodic Titanium Dioxide Films Produced on Ti-6Al-4V Alloy - Vera, Maria Laura (2015)
Ti-6Al-4V alloy with TiO2 coating is the most commonly selected material to construct an aortic heart valve. Wear resistance is the main mechanical property to be evaluated for this purpose. In this paper, the wear resistance of TiO2 thin films obtained by anodic oxidation of Ti-6Al-4V is evaluated. Anodic oxidation was performed at 20 V to 70 V with a H2SO4 1 M electrolyte. The samples were thermally treated at 500°C for 1 h, and crystalline phases of TiO2 were obtained. The wear was performed in a ball-on-flat recip‐ rocating machine with a range of loads from 1 gf to 4 gf and times between 60 s and 1200 s, using a diamond sphere as counterface. The counterface oscillates at 0.5 Hz and 4 mm in amplitude. The wear is measured using a profilometer and is calculated as the worn volume. The wear resistance of the coated samples is larger than the substrate, and increases with thickness and with crystalline coating.